Generative sustainability: a human resource framework to navigate the future of work - Sagan, Michele Adelene (2025)
The Future of Work (FoW) has raised concerns about sustainability, leading to significant changes in the workplace. Key megatrends such automation displacing routine tasks, gig work transforming employer-employee contracts, remote and hybrid work impacting employee management, and environmental, social and governance (ESG) concerns driving various diversity, equity and inclusion (DEI), corporate social responsibility (CSR) and sustainability initiatives, are all impacting organisational and workforce resilience. As such, implementing future-proofed human resource management (HRM) practices can help navigate FoW challenges. Adopting an interpretivist-constructivist thinking, this research utilised a qualitative approach in the form of semi-structured interviews with 39 senior managers and human resource professionals from organisations implementing ESG, CSR and FOW practices. Data collected was then analysed through a qualitative analysis software.